Pellet Quality with the Addition of Kepok Banana Peel Silage in Grower Crossbred Native Chickens Diet - T. N. I. Koni; T. A. Y. Foenay (Jurnal Sain Peternakan Indonesia, 2022)
Kepok banana peel is one food processing waste that can be used as poultry feedstuff. The content of fiber and tannins in banana peels limits its utilization, and the fermentation process can improve the nutritional quality of banana peels. Crossbred native chickens feed usually available in three forms mash, granules, and pellets. The nutrient content of the feed ingredients used in the manufacture of pellets will affect the quality of the pellets produced. This study aimed to examine the use of banana peel silage on pellets' physical and nutritional quality for crossbred native chickens in the grower phase. This experiment used a completely randomized design with four treatments and five replications. The four treatments were (P0) diet without banana peel silage, (P1) diet with 10% banana peel silage, (P2) diet with 20% banana peel silage, (P3) diet with 30% banana peel silage. Data were analyzed by analysis of variance and continued with Duncan's New Multiple Range Test. The results showed that the level of banana peel silage had a very significant effect (p<0.01) on the pellet durability, pellet density,  moisture content, crude fiber, and crude fat pellet. It was concluded that kepok banana peel silage up to 30% in the crossbred native chicken feed positively impacted pellet durability, density, moisture content, fat content, crude protein content, and reduced crude fiber content.